Cyfip1 Haploinsufficiency Increases Compulsive-Like Behavior and Modulates Palatable Food Intake in Mice: Dependence on Cyfip2 Genetic Background, Parent-of Origin, and Sex. Issue 9 (1st September 2019) - Babbs, Richard K; Beierle, Jacob A; Ruan, Qiu T; Kelliher, Julia C; Chen, Melanie M; Feng, Ashley X; Kirkpatrick, Stacey L; Benitez, Fabiola A; Rodriguez, Fred A; Pierre, Johanne J; Anandakumar, Jeya; Kumar, Vivek; et al.
Abstract: Binge eating (BE) is a heritable trait associated with eating disorders and involves episodes of rapid, large amounts of food consumption. We previously identified cytoplasmic FMR1-interacting protein 2 ( Cyfip2 ) as a genetic factor underlying compulsive-like BE in mice. CYFIP2 is a homolog of CYFIP1 which is one of four paternally-deleted genes in patients with Type I Prader-Willi Syndrome (PWS), a neurodevelopmental disorder whereby 70% of cases involve paternal 15q11-q13 deletion. PWS symptoms include hyperphagia, obesity (if untreated), cognitive deficits, and obsessive-compulsive behaviors. We tested whether Cyfip1 haploinsufficiency (+/−) would enhance compulsive-like behavior and palatable food (PF) intake in a parental origin- and sex-dependent manner on two Cyfip2 genetic backgrounds, including the BE-prone C57BL/6N ( Cyfip2 N/N ) background and the BE-resistant C57BL/6J ( Cyfip2 J/J ) background. Cyfip1 +/− mice showed increased compulsive-like behavior on both backgrounds and increased PF intake on the Cyfip2 N/N background. In contrast, maternal Cyfip1 haploinsufficiency on the BE-resistant Cyfip2 J/J background induced a robust escalation in PF intake in wild-type Cyfip1 J/J males while having no effect in Cyfip1 J/- males. Notably, induction of behavioral phenotypes in wild-type males following maternal Fmr1 +/− has previously been reported. In the hypothalamus, there was a paternally-enhanced reduction in CYFIP1 protein whereas in the nucleus accumbens, there was a maternally-enhanced reduction in CYFIP1 protein. Nochange in FMR1 protein (FMRP) was observed in Cyfip1 +/− mice, regardless of parental origin. To summarize, Cyfip1 haploinsufficiency increased compulsive-like behavior and induced genetic background-dependent, sex-dependent, and parent-of-origin-dependent effects on PF consumption and CYFIP1 expression that could have relevance for neurodevelopmental and neuropsychiatric disorders.